2015 SID Honors and Awards. Issue 2 (1st March 2015) - Donelan, Jenny
Abstract : This year's winners of the Society for Information Display's Honors and Awards include Junji Kido, who will receive the Karl Ferdinand Braun Prize for his outstanding contributions to the science and technology of OLEDs and pioneering contributions to commercializing white OLEDs for general lighting applications; Shohei Naemura, who will be awarded the Jan Rajchman Prize for his outstanding achievements in the chemical physics of liquid crystals and contributions to research on LCDs; Ingrid Heynderickx, who will receive the Otto Schade Prize for her outstanding contributions to the measurement, specification, and improvement of the image quality of electronic‐display technologies; Jin Jang, who will be awarded the Slottow–Owaki Award for his major contributions to display education and active‐matrix‐display development, including AMOLED displays, AMLCDs, and flexible displays; and Allan R. Kmetz, who will receive the Lewis and Beatrice Winner Award for his exceptional and sustained service to the Society for Information Display.